2019
DOI: 10.1158/1541-7786.mcr-18-1045
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of HCC Mouse Models: Towards an Etiology-Oriented Subtyping Approach

Abstract: Murine liver tumors often fail to recapitulate the complexity of human hepatocellular carcinoma (HCC), which might explain the difficulty to translate preclinical mouse studies into clinical science. The aim of this study was to evaluate a subtyping approach for murine liver cancer models with regard to etiology-defined categories of human HCC, comparing genomic changes, histomorphology, and IHC profiles. Sequencing and analysis of gene copy-number changes [by comparative genomic hybridization (CGH)] in compar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 53 publications
(73 reference statements)
1
26
0
Order By: Relevance
“…This blue light treatment followed by promotion of melatonin secretion at night inhibited tumor growth in xenograft rat models with Morris 7288CTC hepatoma although detailed mechanisms are undefined . Diethylnitrosamine (DEN) administration is utilized to induce HCC in rodents as an animal model of HCC . A previous study administered melatonin (5 or 10 mg/kg per day for 10, 20, 30, or 40 weeks via i.p.…”
Section: Functional Roles and Therapeutic Potentials Of Melatonin Andmentioning
confidence: 99%
See 1 more Smart Citation
“…This blue light treatment followed by promotion of melatonin secretion at night inhibited tumor growth in xenograft rat models with Morris 7288CTC hepatoma although detailed mechanisms are undefined . Diethylnitrosamine (DEN) administration is utilized to induce HCC in rodents as an animal model of HCC . A previous study administered melatonin (5 or 10 mg/kg per day for 10, 20, 30, or 40 weeks via i.p.…”
Section: Functional Roles and Therapeutic Potentials Of Melatonin Andmentioning
confidence: 99%
“…83 Diethylnitrosamine (DEN) administration is utilized to induce HCC in rodents as an animal model of HCC. 84 A previous study administered melatonin (5 or 10 mg/kg per day for 10, 20, 30, or 40 weeks via i.p. injection) to DEN mice and demonstrated that melatonin inhibited HCC development and improved liver conditions during DEN-induced liver injury.…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
“…6e, f), confirmed by histologic analyses. Interestingly, tumor lesions in FFC-fed Mcl1 Δhep mice differed from tumors in chow-fed Mcl1 Δhep mice 8,29 in respect to their growth pattern which frequently lacked distinct borders (Fig. 6g, left and middle image) but often showed nodule-in-nodule appearance (Fig.…”
Section: Mcl1 Deficiency In Hepatocytes Promotes Tumor Development Inmentioning
confidence: 99%
“…Therefore, a "second-hit" usually consisting of a chemical hepatotoxin is required for progression of ALD to cirrhosis and/or HCC. Indeed, of the hepatotoxins, DEN-induced C57BL/6 tumours have recently been matched to most resemble alcohol-induced HCC both morphologically and by comparative genomic hybridisation in a study comparing five different HCC models with human data [47] . Ambade et al [48] established a model of alcohol-driven HCC in adult C57BL/6 male mice.…”
Section: Ald-associated Hcc Modelsmentioning
confidence: 99%